Evaluation of low-cost sensors for real-time water quality monitoring - Xavier, Felipe Natã de Camargo; Martins, Leila Droprinchinski; Oyamada, Marcio Seiji; Spanhol, Fabio Alexandre; Coutinho, Fábio Rizental; Pfrimer, Felipe Walter Dafico; de Camargo, Edson Tavares (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2022)
Low-cost sensors have the potential to significantly reduce costs compared to reference devices. The problem, however, is that measurements from low-cost sensors can be unreliable when it comes to certifying water quality. This work investigates the possibility of using low-cost sensors to monitor water quality parameters and automate the monitoring process through the concept of the Internet of Things (IoT). The sensors evaluated are turbidity, temperature, dissolved oxygen and hydrogen potential. The evaluation of the sensors was performed both in a controlled environment with standard solutions and in a real environment. The results show that the sensors provide readings that are close to reference values when tested in a controlled environment, but some challenges remain when tested in the real world.